Material point method for crack propagation in anisotropic media: a phase field approach - Kakouris, E.G.; Triantafyllou, S.P. (Springer, 2018)
A novel phase field formulation implemented within a material point method setting is developed to address brittle fracture simulation in anisotropic media. The case of strong anisotropy in the crack surface energy is treated by considering an appropriate variational, i.e., phase field approach. Material point method is utilized to efficiently treat the resulting coupled governing equations. The brittle fracture governing equations are defined at a set of Lagrangian material points and subsequently interpolated at the nodes of a fixed Eulerian mesh where solution is performed. As a result, the quality of the solution does not depend on the quality of the underlying finite element mesh and is relieved from mesh-distortion errors. The efficiency and validity of the proposed method is assessed through a set of benchmark problems.